Financial liberalization and economic growth in the ECOWAS Sub-Region - Eghosa Lawson Igbinovia; Ikponmwosa Michael Igbinovia (Journal of Enterprise and Development, 2023)
Purpose — The study examines the nexus between financial liberalization and the economic growth of ECOWAS member states. Method — The longitudinal and latitudinal survey research design (expo-facto) is used in this study. Data are sourced from the World Bank and IMF Data Set for 2012-2020 and employed panel co-integration and system GMM for analyses. Result — We found that financial liberalization significantly impacts the economic growth of selected ECOWAS member countries. Similarly, the domestic economy's openness significantly impacts economic growth. While financial development exerts a positive impact, exchange rate and inflation negatively impact economic growth, the impact of interest rate is positive but insignificant. Contribution — The study provides cross-country evidence on the empirical nexus between financial liberalization and the economic growth from ECOWAS member states. To the best of authors’ knowledge, the study is one of the few studies on cross-country financial liberalization and the economic growth and used the panel data regression analysis. By this, the study covers a methodological gap, using a technique that can account for endogeneity and omitted variable problem.